2013
DOI: 10.3109/1547691x.2013.789939
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of essential oil ofSatureja khuzistanica:In vitrocytotoxicity and anti-microbial activity

Abstract: In nature, essential oils play an important role in the protection of the plants by exerting anti-bacterial, -viral, -fungal, -oxidative, -genotoxic, and free radical scavenging properties, as well as in some cases acting as insecticides. Several Satureja species are used in traditional medicine due to recognized therapeutic properties, namely anti-microbial and cytotoxic activities. The purpose of the present work was to determine the biologic activity of the essential oil of S. khuzistanica Jamzad (Lamiaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The results confirm the SEOs activity against multidrug bacterial strains. According with other studies [24,53,54], as reported in Table 7, MIC and MBC values ranged from 0.39 to 6.25 mg•mL −1 . Commercial SEOT showed the lowest MIC and MBC values towards Gram-positive and Gram-negative bacteria.…”
Section: Antibacterial Activity Of Eos and Nessupporting
confidence: 58%
“…The results confirm the SEOs activity against multidrug bacterial strains. According with other studies [24,53,54], as reported in Table 7, MIC and MBC values ranged from 0.39 to 6.25 mg•mL −1 . Commercial SEOT showed the lowest MIC and MBC values towards Gram-positive and Gram-negative bacteria.…”
Section: Antibacterial Activity Of Eos and Nessupporting
confidence: 58%
“…Another plant species investigated fot its cytotoxic activity is S. khuzestanica (Yousefzadi et al, 2014). Essential oil of this plant significantly reduced cell viability of Vero, SW480, MCF7, and JET 3 cells in a dose-dependent manner; IC 50 values calculated for each cell types were 31.2, 62.5, 125, and 125 mg/mL.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Nineteen compounds were presented among which carvacrol was the main component (92.87%) followed by limonene (1.2%) (12).…”
Section: Resultsmentioning
confidence: 99%
“…The essential oil of this plant has been reported for a number of biological activities, including: antibacterial, antifungal, anti-leishmanial, anticancer, antioxidant, anti-inflammatory, anti-diabetic, antihyperlipidemic and antispasmodic properties (11,12). The antibacterial activity of S. khuzestanica essential oil has been shown against a number of bacteria including Grampositive food pathogens, some members of Enterobacteriaceae, as well as Pseudomonas aeruginosa (13,14).…”
Section: Introductionmentioning
confidence: 99%